A little bit of marketing history repeating: The effect of word of mouth marketing in social networks. Issue 2 (12th January 2015) - Unknown
Abstract : Purpose: – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: – The effect of 'word of mouth' on publicising a product or service has achieved almost mythical status for marketers and marketing researchers alike. From the 'sleeper hit' of films such as The Shawshank Redemption to the rapid spread of successful brands of cigarettes or chocolate bars, everyone involved in understanding the how and the why of selling goods have been fascinated by a seemingly impenetrable phenomenon. Practical implications: – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organisations. Originality/value: – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.